2021
DOI: 10.1021/acsmaterialslett.1c00138
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Carbazole: Origin, Impurity, and Properties

Abstract: Photoluminescence quantum yield (PLQY) is one of the most important characteristics for organic luminescent materials. However, when carbazole prepared from the lab was compared to that from a commercial source, a remarkable change of PLQY was observed to vary from 37.1% to 69.8%. Taking 9-(4-bromo­benzyl)-9H-carbazole (CzBBr) as an example of carbazole derivatives, the PLQYs of CzBBr synthesized from different origins of carbazole were varied from 16.0% to 91.1%. Our studies demonstrated that efficient radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 28 publications
1
49
0
Order By: Relevance
“…Our experimental results agreed well with Liu's report. [ 1c,9 ] Differently, the typical ultralong phosphorescence bands at 552, 604, and 661 nm were the intrinsic phosphorescence of Bd derivatives’ radical cations, and 2CzBr activated their intrinsic ultralong phosphorescence probably by the heterojunction. The formation of heterojunction required close proximity of matrix and dopant for easy electron communication to accelerate in generating and stabilizing Bd derivatives’ radical cations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experimental results agreed well with Liu's report. [ 1c,9 ] Differently, the typical ultralong phosphorescence bands at 552, 604, and 661 nm were the intrinsic phosphorescence of Bd derivatives’ radical cations, and 2CzBr activated their intrinsic ultralong phosphorescence probably by the heterojunction. The formation of heterojunction required close proximity of matrix and dopant for easy electron communication to accelerate in generating and stabilizing Bd derivatives’ radical cations.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Liu et al recently reported their findings that the commercially available carbazole was inevitably mixed with trace carbazole isomer (1H‐benzo[f]indole, Bd), and Bd was believed to be involved in the origination of UOP. [ 1c,9 ] They suggested that Cz and Bd moieties in close proximity acted as a microplanar heterojunction to generate photo‐induced charge‐separated states, and further to produce intense UOP. Based on their results, the UOP of carbazole derivatives previously presented in the literature are actually integrated luminescent properties of carbazole derivatives and Bd's counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the effects of trace amounts of carbazole isomers,w ea lso synthesized carbazole from 2-nitro-1,1'biphenyl to prepare Lab-CzBH and Lab-CzBMe. [51] Indeed, poor afterglow performances of Lab-CzBH and Lab-CzBMe were observed by the naked eye (Figure S28). But, the trimode emission can be still observed when the delay time is less than 5ms( Figure S29).…”
Section: Methodsmentioning
confidence: 99%
“…[19] Further research demonstrated that dopant doping is very effective in realizing high quantum yield, long-lived phosphorescent, and fluorescent organic materials. [31] Dibenzothiophene (DBT), a heterocyclic aromatic compound that is similar to Cz with its central pyrrole ring substituted by a thiophene ring, is an electron-donating moiety with good hole-transporting ability and high triplet energy, which was reported to be a phosphor exhibiting weak RTP in the crystal state. [4] DBT has been derivatized into various compounds exhibiting excellent performance in their respective fields, such as 2,8-bis(diphenylphosphoryl)dibenzo[b,d]thiophene (PPT) which is well applied as a highly efficient host material in OLED device, [16] and dibenzo[b,d]thiophen-2-yl(phenyl) methanone (BDBT) derivatives that are reported as promising Doping has shown very promising potential in endowing room-temperature phosphorescence (RTP) properties of organic phosphors with minimal effort.…”
Section: Doi: 101002/adma202201569mentioning
confidence: 99%
“…[ 19 ] Further research demonstrated that dopant doping is very effective in realizing high quantum yield, long‐lived phosphorescent, and fluorescent organic materials. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%